Septal Bounce as an Echocardiographic Finding: Report of Two Clinical Cases. - P. A., Moreno Velazco; D. A., Belmontes Gutiérrez; J. J., Acosta Castor; L.A., Camacho Cruz; S. A., Almanza Luna; A., Ramírez Salazar A. (Revista de Ciencias Médicas Torreón, 2025)
Septal bounce is an abnormal interventricular septal motion pattern seen on echocardiography, characterized by an abrupt protodiastolic oscillation. Classically associated with constrictive pericarditis, it can also be observed in other clinical contexts such as ventricular dyssynchrony, severe pulmonary hypertension, previous cardiac surgeries, and restrictive cardiomyopathies. This article presents two clinical cases where the echocardiographic finding of septal bounce was key in guiding the differential diagnosis and clinical decision-making. A comprehensive literature review is also provided, exploring the pathophysiology, diagnostic value, and clinical utility of this sign.